2015
DOI: 10.1063/1.4933060
|View full text |Cite
|
Sign up to set email alerts
|

Ionization and photofragmentation of Ru3(CO)12 and Os3(CO)12

Abstract: In this paper, we use a combination of photoelectron spectroscopy, mass spectrometry, and density functional theory calculations to get a detailed understanding of valence single and double ionization and the subsequent dissociation processes. This is exemplified on benchmark systems, trimetallo-dodecacarbonyls M 3 (CO) 12 with M = Ru, Os, where the energy remaining in the molecule after photoionization can be retrieved by measuring the degree of fragmentation of the molecular ion. The intensity of different m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
(80 reference statements)
1
6
0
Order By: Relevance
“…We proposed that the Os–CO might be an ideal internal reference for quantitative SERS analysis for the following reasons: (1) CO has very a high force constant (1860 N/m), and (2) the Os 3 cluster core has a highly rigid structure. , Moreover, because Os–CO has only one binding site (via the sulfido group) for gold substrate, it can be well embedded as a molecular layer sandwiched in between the gold layers of the substrate. Thus, as an internal reference, Os–CO will not be influenced by the outer environment, for example, via dynamic displacement by the analyte.…”
Section: Results and Discussionmentioning
confidence: 99%
“…We proposed that the Os–CO might be an ideal internal reference for quantitative SERS analysis for the following reasons: (1) CO has very a high force constant (1860 N/m), and (2) the Os 3 cluster core has a highly rigid structure. , Moreover, because Os–CO has only one binding site (via the sulfido group) for gold substrate, it can be well embedded as a molecular layer sandwiched in between the gold layers of the substrate. Thus, as an internal reference, Os–CO will not be influenced by the outer environment, for example, via dynamic displacement by the analyte.…”
Section: Results and Discussionmentioning
confidence: 99%
“…A potential strength, however, may be photon energy dependent fragmentation of precursor molecules, which has potential to further enhance the in-situ purity of the resulting FXBID deposits. It has been shown that X-ray induced fragmentation of certain relevant precursor molecules exhibits photon energy dependency not only in terms of fragmentation rates, but also fragmentation chemistry, i.e., changing relative intensities of various fragments [103,118,119]. Such effects could be exploited to select photon energies for FXBID that result in a high ratio of low mass fragments (in ideal cases only the metal center itself) versus high mass fragments leading to implantation of a large amount of alien atoms from the ligands into the resulting deposits.…”
Section: Perspectives Or: What Fxbid Might Be Good Formentioning
confidence: 99%
“…It acts as a catalyst for a wide range of reactions [15]. It was considered as a model system for studies of mechanisms of photoinduced reactions [16][17][18] and vibrational and NMR spectroscopy [19][20][21]. In crystal, which is reported to have a monoclinic space group P2 1 /n, the Os 3 (CO) 12 molecules show approximate (pseudo-) D 3h symmetry, where the three Os atoms form an almost equilateral triangle [22].…”
Section: Introductionmentioning
confidence: 99%